The Distributed Ledger Technology : A Futuristic Accounting - Misra, Dr. Pushpendra; Gupta, Dr. Anshu (The journal of contemporary issues in business and government, 2023)
The future of accounting profession, the Automation in accounting, the emphasis on professional development in technology and soft skills, the workplace flexibility & the accounting firms start hiring for roles that have not been typical. (Future of Jobs Report ,2018). The technology-based accounting practices, allows for a distributed database that holds a growing number of records. The objectives of this study are to explorer the future of accounting practices, understand the blockchain technology and its working in accounting practices and identify the opportunities and challenges of the distributed ledger practices. For the completion of research work secondary data is used.